Application of the Milan System for Reporting Salivary Gland Cytopathology: A systematic review and meta‐analysis. Issue 11 (30th May 2022) - Wang, Zhaoyang; Zhao, Huan; Guo, Huiqin; An, Changming
Abstract : Background: The Milan System for Reporting Salivary Gland Cytopathology (MSRSGC) is a standard, evidence‐based classification system for salivary gland fine‐needle aspiration (SG‐FNA). Since it was published in 2018, many researchers across the world have applied this uniform reporting system to their cohorts. Methods: The authors comprehensively reviewed cohort studies conducted since publication of the MSRSGC and performed a meta‐analysis. The risk of neoplasm and the risk of malignancy (ROM) were calculated for each diagnostic category, and their diagnostic efficacy was evaluated. Results: Thirty‐five studies were included in the meta‐analysis. The total number of SG‐FNAs was 10, 706, and 7168 of those had histopathologic follow‐up. The ROM for each category was: nondiagnostic, 11.4%; nonneoplastic, 10.9%; atypia of undetermined significance, 30.5%; neoplasm–benign, 2.8%; neoplasm–salivary gland neoplasm of uncertain malignant potential, 37.7%; suspicious for malignancy, 83.8%; and malignant, 97.7%. Low‐level heterogeneity was observed in ROM estimation. The sensitivity, specificity, and diagnostic odds ratio for differentiating malignant and benign lesions were 88.0%, 98.5% and 520.3, respectively. Conclusions: The reporting of SG‐FNA using the MSRSGC demonstrated high diagnostic accuracy. The ROM for each category was generally concordant with the recommendations, except for the suspicious for malignancy category, which was significantly higher than the reference value. The tiered, standardized classification system would benefit the clinical management of salivary gland lesions. Abstract : Reporting salivary gland fine‐needle aspiration using the Milan System for Reporting Salivary Gland Cytopathology demonstrated high diagnostic accuracy. The risk of malignancy for each category was generally concordant with the recommendations, except for the category suspicious for malignancy, which was significantly higher than the reference value.